Differences Between Girls and Boys in the Disclosure of Sexual Violence - Hietamäki, Johanna (Journal of interpersonal violence, 2024)
This article addresses the differences between girls and boys in the disclosure of sexual violence. The dataset combines data from the Finnish Child Victim Survey (FCVS) of 2008 (N = 13,459) and 2013 (N = 11,364), focusing on victims of sexual violence, ages 11 to 17 years, from the perspectives of disclosure and gender. Frequency and percentage analysis, cross tabulation, and a Chi-square test were used in the analysis. In the FCVS for both years, around 85% of the victims were girls. In almost two-thirds of the cases, the offender was a relative, friend, or some other known person, while in more than one-third of the cases, the offender was unknown to the victim. The second most common case was that the victim knew the offender, who was not, however, a friend. Sexual violence was found to be, in many ways, gendered. Most of the victims were girls, and most of the offenders were men. There was also a gender difference in the disclosure of experiences. Twenty-one percent of the girls and 45% of the boys reported that they had not told anyone about their experiences. Irrespective of the type of offender, the victims most often (63%) told a peer about their experiences, while 23% told parents, and only 10% told authorities. Moreover, victims reported shame and fear, distrust toward adults, and disbelief that disclosure would be helpful as reasons for not disclosing their experiences. To address this problem, raising awareness of the phenomenon, promoting an atmosphere that supports disclosing experiences of sexual violence, and improving readiness to address them are required.